-1

enter image description here

I think I got it, could you take a look, please.

1
  • 1
    What have you tried? – Graham Kemp Apr 2 at 10:48
0

Let's start you on your journey. You want to derive a negation. Use a proof by negation introduction. Assume Tmm, introduce an existential, and then use the premises to derive the contrary too.

|  (∃x)(Rx)                           (Premise)
|  (∃x)(~Sx)                          (Premise)
|_ (∀x)(∀y)(~(Rx → Sy) → ~(∃z)(Tmz))  (Premise)
|  |_ Tmm                              (Assumption)
|  |  (∃z)(Tmz)                        (Existential Introduction)
|  |  :
|  |  :
|  |  ~(∃z)(Tmz)                       (Negation Introduction)
|  |  #                                (Negation Elimination)
|  ~Tmm                                (Negation Introduction)

I have followed your steps and also uploaded where I get stuck. Could you take a look and give me some suggestions, please. Thank you – Stanley

1   |   (Ex)Rx                             Premise
2   |   (Ex)~Sx                            Premise
3   |_  (Ax)(Ay)(~(Rx > Sy) > ~(Ez)Tmz)    Premise
4   | |_  Ra                               Assumption
5   | | |_  ~Sb                            Assumption
6   | | |   (Ra & ~Sb)                     4,5  &I
    : : :

That is not according to my advice. My suggested goal is to derive ~(Ez)Tmz so that you can derive a contradiction under the assumption of Tmm. You could do that if you could derive ~(Ra > Sb); since universal eliminations of the third premise gives ~(Ra > Sb) > ~(Ez)Tmz . So... try that.

 1   |   (Ex)Rx                             Premise
 2   |   (Ex)~Sx                            Premise
 3   |_  (Ax)(Ay)(~(Rx > Sy) > ~(Ez)Tmz)    Premise
 4   |  |_ Tmm                              Assumption
 5   |  |  (Ez)Tmz                          E Introduction 4
 6   |  |  |_ Ra                            Assumption
 7   |  |  |  |_ ~Sb                        Assumption
 8   |  |  |  |  |_ Ra > Sy                 Assumption
     :  :  :  :  :  :
     :  :  :  :  :
 m   |  |  |  |  ~(Ez)Tmz                   :
 n   |  |  |  ~(Ez)Tmz                      E Elimination 2,7-m
 o   |  |  ~(Ez)Tmz                         E Elimination 1,6-n
 p   |  |  #                                ~ Elimination 5,o
 q   |  ~Tmm                                ~ Introduction 4-p
4
  • Hi Graham Kemp, I have followed your steps and also uploaded where I get stuck. Could you take a look and give me some suggestions, please. Thank you – Stanley Apr 2 at 19:14
  • Hi, I tried it and I think I got it. Could you take a look and check it? – Stanley Apr 3 at 5:22
  • Also, I have another question posted if you can take a look.philosophy.stackexchange.com/questions/81003/… – Stanley Apr 3 at 6:55
  • ... Just use Conditional Elimination. Ra, (Ra -> Sb) |- Sb, so therefore Ra, ~Sb |- ~(Ra -> Sb) – Graham Kemp Apr 3 at 9:19
1

Well, at a broad level, ∀x ∀y [~(~Rx ∨ Sy) → ~(∃z Tmz)] is equivalent to ∀x ∀y [(Rx ∧ ~Sy) → ~(∃z Tmz)]. Your other two premises tell you that there is an x and a y such that (Rx ∧ ~Sy). This implies the conclusion, ~(∃z Tmz). This is equivalent to ∀z ~Tmz, and then you can instantiate z with m, yielding ~Tmm.

Your proof should generally follow that logic. You just need to translate each step into a Fitch proof in your system.

7
  • I only know (∃x)Rx and (∃x)~Sx can be combined to ((∃x)Rx & (∃x)~Sx), but this can not imply ~(∃z Tmz) because they are not ∀x ∀y ~(Rx → Sy). Could you tell me what move should I take to make it happen? Thank you – Stanley Apr 2 at 18:58
  • @Stanley you first need to use existential elimination on the first two premises to obtain Rx ∧ ~Sy (where x and y have not yet been used as free variables). Then use universal elimination to obtain (Rx ∧ ~Sy) → ~(∃z Tmz). – causative Apr 2 at 19:03
  • Ok, I got the result of (∃x)(∃y)(Rx & ~Sy), but can I use universal elimination directly to (∀x)(∀y)~(Rx → Sy) → ~(∃z)Tmz? since it is a conditional sentence. – Stanley Apr 2 at 19:43
  • @Stanley you need to use existential elimination, to go from (∃x)(∃y)(Rx & ~Sy) to just Rx & ~Sy (where x and y have not been used as free variables before in your proof). – causative Apr 2 at 20:10
  • 1
    @Stanley logic.stanford.edu/intrologic/notes/chapter_08.html scroll down to where it says "existential elimination." The rule is that from ∃x p(x), you can derive the plain expression p(x), provided you have not previously used x as a free variable. (If you have already used x as a free variable you would instead instantiate as p(y) or p(w) or something you haven't used.) – causative Apr 2 at 22:03

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.